The Impact of Artificial Intelligence Tools on English Language Acquisition Among University Students: A Survey-Based Study - Widad omar Ali (Surman Journal of Science and Technology, 2025)
Language learning has changed in the digital era, AI techniques have been incorporated in teaching and are helping to pave the way toward more personalized, autonomous learning. This research examines the influence of AI tools on the learning of English as well as the use habit, the perceived effectiveness and the aspects of language skills enhanced by AI among university students. A quantitative approach was adopted using survey-guided questionnaires with 21 undergraduate students from diverse academic backgrounds. The descriptive statistics and chi-square tests were used to analyze the data. The results show that a large majority of students (81 %) use AI tools actively, and more than 50 % of these students think AI-based tools help them learn English. Statistically, AI being used and perceived effectiveness were above chance level (p > 0.05); perceived contributions for the four core skills—reading, writing, vocabulary, and listening—did not differ statistically. This finding is consistent with the assumption that AI tools are commonly valued and utilized, although the use may not be as task specific. The study suggests the need for careful consideration of the role AI should play within pedagogical settings to support equitable language development and to encourage critical literacy of technology.